Dehorning rhinos as a theoretical game - Lee, T; Roberts, D (Elsevier, 2016)
The poaching of rhinos has increased dramatically in recent years, creating an ongoing problem and cost to rhino managers. A manager may decrease the reward to the poacher by devaluing the horn such as dehorning so that only a stub is left, or inserting a poison, dye or GPS tracker. However, as it is impossible to remove all value of the horn (a stub remains, poison fades, or GPS trackers can be removed) a poacher may still kill the rhino for the partial gain from the horn, and to avoid tracking this particular rhino in the future. We consider the problem as a theoretical game, where the players are poachers and a rhino manager. By considering the payoff to both manger and poachers we highlight the manager's struggle to discourage poachers to not kill a devalued rhino, despite the loss of time, and increase of risk, to the poacher. Generally, the manager can only influence the situation if virtually all rhino horns are devalued, or the risk involved to the poacher is increased, such as through greater enforcement. However, the cost to devalue the last few rhinos may be very costly due to the sparsity of rhinos, and the rhino manager can easily make a loss by trying to devalue the last, few rhinos. But, whilst a few rhinos remain with their intact horn, a poacher is unlikely to avoid a particular ranch.